Algebraic research in the works of members of the Kyiv Physical and Mathematical Society in the first years of its existence - T. S. Kletska (History of science and technology, 2018)
The article is devoted to the review, analysis and systematization of the generalization of materials that characterize the development of algebraic research and teaching of algebra at the beginning of the life of the University of St. Vladimir in Kyiv. Particular attention was paid to the research of the members of the Kyiv Physical and Mathematical Society, as the most active faculty of natural sciences scientists of the time in Kyiv. Historical, systematic and biographical methods were used to prepare the work, which allowed to systematize, classify and evaluate the sources used, compare the evaluation of the results of the members of the Kyiv Physical and Mathematical Society with various authors, highlight the main directions and state of coverage of the topic, as well as the results of other historians of science, review previous work on this issue and clearly identify issues that have not been resolved. The analysis of the sources allowed the author to give an objective assessment of the contribution of members of the society to the development of algebra and methods of teaching it. It was shown that despite the lack of trained specialists and other problems, the level of teaching of this discipline was quite high. Various researches of Kyiv mathematicians are analyzed. It was shown that algebra was one of the most popular directions of the mathematicians of the Kyiv university, although not the most effective one.  On the basis of comparison of the characteristics of various researchers who studied the work of the Kyiv Physical and Mathematical Society, his role in creating a system of higher mathematical education in the territory of Ukraine is shown. It was established that due to the personal contribution of the members of the society, the foundations for the future Kyiv algebraic school were laid. Detailed works on the algebra of the time printed in Kyiv are considered in detail. It was shown that the society itself became the center around which the most active scholars and teachers met, in which the directions of research of the Kyiv mathematicians were formed. It should also be noted that the company's activities contributed to the birth of the Kyiv Mathematical School.